(untitled) (Research, Society and Development, 2020)
This article addresses the problem of drug use by students at a public school and the preventive actions taken by the school community to minimize this problem. The study had as a locus, a Full-time High School, located in the district of Mangabeira, municipality of Eusébio - Ceará. It aimed to identify the factors that lead young people to use drugs, in order to develop a diagnosis that points out the panorama of drug use at school, the risk and protection factors involved. For data collection, semi-structured questionnaires related to the theme of drugs were used during the 2019 academic period. The analysis of statistical data was performed using the GraphPad Prism 6 software. The level of significance was set at p <0.05 , considering the 95% confidence interval for all tests. The results point out as the main risk factor for the use of legal and illegal drugs the influence of friendships caused by lack of parental monitoring, absence of family and school partnership. Meanwhile, the main protective factors are family support, school and social programs. Through this study, we believe that we have contributed to the school and family to reflect on their role, the implications of drugs in society, contributing to the cultural, political and economic transformation of society.